Bridging Aristotelian Logic and Islamic Jurisprudence: A Comparative Analytical Study of Qiyās and Logical Reasoning in Light of Qiyās Al-Wāsiʿ (Contrarius Series: Law & Social Justice, 2026)
This research examined logic and the role of Muslim scholars in establishing analogy through it, using it as a jurisprudential approach to its applications in Islamic jurisprudence. It also examined how Muslim scholars used Aristotelian logic in the buildup of the foundation of Islamic logical reasoning and the principles of jurisprudence. It took into account the concept of analogy: its application to Islamic jurisprudential reality, in all emerging jurisprudential issues or various unstated textual matters in the lives of Muslims. The research also focused on the foundations from which analogy is derived in its broad sense, explaining its characteristics that distinguish it from other sources of legislation, on the one hand, and from logic, on the other. It also highlighted the role of Muslim scholars, such as Imām al-Ghazālī and others, in establishing analogy from logic, as well as establishing a theory for deriving rulings on new developments in Muslim reality that are not explicitly stated, to be valid for all times and places. The research followed an inductive approach, collecting, evaluating, and comparing information, then analyzing and interpreting it to arrive at its intended conclusion. The study of the issue of the relationship between logic and analogy relies on the inductive approach. The collected evidence and the opinions upon which it is based are then analyzed using the analytical approach. Using the comparative approach, it draws a comparison between the issues of logic and its relationship to analogy, before explaining the role of Muslim scholars in establishing analogy through it, and the way it is employed and applied in Islamic law.